PERCEIVED BARRIERS IN PHYSICAL ACTIVITIES AMONG UNIVERSITY STUDENTS - Saadan, Rosli; Jano, Zanariah; Sidek, Safiah; Bokhari, Mohamad (Journal of Human Capital Development (JHCD), 2015)
Participating in physical activities is essential for maintaining health and prevention of illness. However, university students tend to spend more time on studying rather than participating in physical activities. The purpose of this study was to identify the constraints of university students engaging in physical activities. A survey was conducted with a total of 600 undergraduate students (n=600) from the Technical University of Malaysia Malacca (UTeM). The sample of students were from three faculties, namely the Faculty of Electrical Engineering (FKE ) ( n = 200), Faculty of Electronics and Computer Engineering ( FKEKK ) ( n = 100 ) and the Faculty of Engineering Technology (FTK) (n = 200 ). An adapted questionnaires on the “Perceived barriers to physical activity among university students” were used for data collection. In comparison to the internal factors, it was found that the external factors are perceived as the main reasons for the barriers of participation in physical activities. Keywords: constraints, physical activity, motivation, support